NLRP3 is involved in long bone edification and the maturation of osteogenic cells. Issue 6 (15th December 2020) - Detzen, L.; Cheat, B.; Besbes, A.; Hassan, B.; Marchi, V.; Baroukh, B.; Lesieur, J.; Sadoine, J.; Torrens, C.; Rochefort, G.; Bouchet, J.; Gosset, M.
Abstract: Overexpression of the nucleotide‐binding leucine‐rich repeat protein 3 (NLRP3) inflammasome in chronic auto‐immune diseases leads to skeletal anomalies, with severe osteopenia due to the activation of osteoclasts. Reproducing this phenotype in Nlrp3 knock‐in mice has provided insights into the role of NLRP3 in bone metabolism. We studied the role of NLRP3 in physiological bone development using a complete Nlrp3 knock‐out mouse model. We found impaired skeletal development in Nlrp3 −/− mice, resulting in a shorter stature than that of Nlrp3 +/+  mice. These growth defects were associated with altered femur bone growth, characterized by a deficient growth plate and an osteopenic profile of the trabeculae. No differences in osteoclast recruitment or activity were observed. Instead,   Nlrp3 −/− femurs showed a less mineralized matrix in the trabeculae than those of Nlrp3 +/+  mice, as well as less bone sialoprotein (BSP) expressing hypertrophic chondrocytes. In vitro, primary osteoblasts lacking NLRP3 expression showed defective mineralization, together with the downregulation of BSP expression. Finally, follow‐up by micro‐CT highlighted the role of NLPR3 in bone growth, occurring early in living mice, as the osteopenic phenotype diminishes over time. Overall, our data suggest that NLRP3 is involved in bone edification via the regulation of hypertrophic chondrocyte maturation and osteoblast activity. Furthermore, the defect appeared to be transitory, as the skeleton recovered with aging. Abstract : We demonstrate an early role of NLRP3 in bone edification using Nlrp3 −/− mice. This effect appears to be due, at least in part, to the involvement of NLRP3 in the maturation, differentiation, and mineralization activity of osteoblasts and in hypertrophic chondrocytes, leading to decreased bone growth. The expression of NLRP3 in these cells is therefore crucial for an optimal ossification during the growth of mice.